2013
DOI: 10.1590/s1519-69842013000200009
|View full text |Cite
|
Sign up to set email alerts
|

The role of a cascade of reservoirs and seasonal variation in the phytoplankton structure in a tropical river

Abstract: This study aims to analyse the influence of a cascade of reservoirs on the density, richness and functional groups of phytoplankton in the Contas River, a tropical river of Brazil. This river has two dams along its course, forming the Pedra and Funil reservoirs. Samples were collected over three consecutive years (Dec., 2007 to Dec., 2010 at 28 sampling stations along the river. We identified 198 species and the stretches downstream from the reservoirs showed greater richness. Chlorophyceae, followed by Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…Acta Limnologica Brasiliensia, 2017, vol. 29, e17 concentration, due to nutrient enrichment and abundant water flow (Moura et al, 2013). A similar relation to the increase in cell density associated with the retention time occurred in the Ernestina reservoir, when the highest densities near the spillway coincide with the longer water retention times in 436 days, from March to June, while the general average found was 198 days.…”
Section: Discussionmentioning
confidence: 52%
“…Acta Limnologica Brasiliensia, 2017, vol. 29, e17 concentration, due to nutrient enrichment and abundant water flow (Moura et al, 2013). A similar relation to the increase in cell density associated with the retention time occurred in the Ernestina reservoir, when the highest densities near the spillway coincide with the longer water retention times in 436 days, from March to June, while the general average found was 198 days.…”
Section: Discussionmentioning
confidence: 52%
“…In SN reservoir, Planktothrix agardhii was dominant during most of the sampling period but had very small representation in AM reservoir. Moura et al (2013) also found that Planktothrix agardhii was dominant in Funil reservoir during the rainy season, overwhelming the concentration of Cylindrospermopsis raciborskii. This may have serious implications for drinking water reservoirs.…”
Section: Discussionmentioning
confidence: 90%
“…The effects of this daily fluctuation on river-reservoir systems are reported by Naliato et al (2009). The high current speed downstream from Itaipu Reservoir caused an intensive dilution of the potamoplankton which developed in lentic sites inside the reservoir, but an increase in richness and abundance can occur in relatively small rivers and downstream from reservoirs with very high water retention times (Moura et al 2013). Lentic stations in reservoirs with long water retention times are generally favorable for phytoplankton blooms composed of r-strategists (Silva et al 2005).…”
Section: Discussionmentioning
confidence: 99%